Test, measurement, and evaluation: Understanding and use of the concepts in education - Dickson Adom; Jephtar Adu-Mensah; Dennis Atsu Dake (Institute of Advanced Engineering and Science, 2020)
Test, measurement, and evaluation are concepts used in education to explain how the progress of learning and the final learning outcomes of students are assessed. However, the terms are often misused in the field of education, especially in Ghana. The objective of the study was to thoroughly explain the concepts to assist educationists and researchers in the field of education to better apply them in educational discourses. The study also suggests best practices in setting test items in measuring students’ learning outcomes while showing policy directions to assist educationists and researchers in the field of educational evaluation.